2022
DOI: 10.1007/s43546-021-00198-8
|View full text |Cite
|
Sign up to set email alerts
|

Dividend announcement effect analysis before and during the COVID-19 pandemic in the Indonesia Stock Exchange

Abstract: The emergence of the SARS-CoV-2 or COVID-19 pandemic has become a challenge for the global society, including the investors in the capital market, due to the uncertainty it has caused. In relation to the phenomenon, this research aimed to examine the impact of COVID-19 pandemic on the dividend announcement effect in Indonesia Stock Exchange by comparing the market volatility around the dividend announcement date of the selected stocks in 2019 and 2020. Implication of dividend increase and decrease as well as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 20 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…In the context of the pandemic crisis, showed that profitability significantly affects dividend policy positively. Therefore, this mediating effect can also create the assumption that the crisis affects dividend policy, mediated by positive profitability (Ashraf, 2021;Cejnek et al, 2021;Cepoi, 2020;Hartono & Raya, 2022;Robiyanto & Yunitaria, 2022;Utomo & Hanggraeni, 2021). Based on the rational basis and the support of the previous studies, the third hypothesis formulated is that GDP has an effect on dividend policy mediated by profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of the pandemic crisis, showed that profitability significantly affects dividend policy positively. Therefore, this mediating effect can also create the assumption that the crisis affects dividend policy, mediated by positive profitability (Ashraf, 2021;Cejnek et al, 2021;Cepoi, 2020;Hartono & Raya, 2022;Robiyanto & Yunitaria, 2022;Utomo & Hanggraeni, 2021). Based on the rational basis and the support of the previous studies, the third hypothesis formulated is that GDP has an effect on dividend policy mediated by profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study by Robiyanto and Yunitaria, (2022) on dividend announcement effect before and during the COVID-19 pandemic in Indonesia discovered that in 2019, the Indonesia capital market presented a weak response toward the event, indicated by the inexistence of abnormal return. Moreover, in 2020, the dividend announcement effect caused negative insignificant abnormal returns and the number of companies with low volatility increased, implying that the stock market was more pessimistic during the pandemic period.…”
Section: Studies On Emerging and Frontier Marketsmentioning
confidence: 99%
“…This indicated buying actions on shares that distribute dividends, which responded quickly and positively. Robiyanto & Yunitaria (2022) reported no significant abnormal return on the distribution by companies indexed LQ-45 in Indonesia. This indicates that the stock market was pessimistic during the pandemic period.…”
Section: Introductionmentioning
confidence: 96%
“…The COVID-19 pandemic has a global impact. At the end of January 2020, the spread of this virus was declared a Public Health Emergency of International Concern (PHEIC) by the World Health Organization (Robiyanto & Yunitaria, 2022). The consequence significantly impacted the global economy as a systemic crisis.…”
Section: Introductionmentioning
confidence: 99%